Asintado - Villanueva, Socorro; Melendez, Aiko; Eigenmann, Gabby; Cuaderno, Miggs; Ignacio, Louie; Ignacio Films (Firm). ([Place of production not identified] Ignacio Films, 2014)
"In the middle of the preparation for Taong Putik Festival, a young man penniless and in love, takes on a drug courier job that goes terribly wrong. To save him, his mother now makes the most difficult decision of her life."
Summary taken from: https://www.imdb.com/title/tt3887408/?ref_=fn_al_tt_2
Produced by Ferdinand Lapuz; music by Danny Tan; cinematography by Louie Ignacio.
Aiko Melendez, Gabby Eigenmann, Miggs Cueaderno.
DVD
In Tagalog
Keywords: Drama